Acoustic control, noise measurement and performance ambition: issues surrounding noise exposure for musicians - Chan, Cheong Jan; Tey, Ming Luan; Hood, Made Mantle (American-Eurasian Network for Scientific Information, 2014)
Unlike manufacturing industries, assessing noise exposure in the performing arts scene is complicated by the fact that sound is the intended product in the work field. Despite existing studies on noise exposure and risk of hearing impairment among musicians (Russo F.A. 2012, Pawlaczyk-Łuszczyńska M. 2011, Emmerich E. 2008, Lee J. 2005), there is yet an account that approaches the topic from a music performer’s/producer’s perspective. Notwithstanding the known facts of musicians being endangered by the sounds they produce, the mechanism of how sounds travel ‘geographically’ in a rehearsal and performance venue, and from which directions and who is affected, has not been included in research designs until now. More intriguing is the fact that a sound produced musically, even at the intensity of 95 dB and above, is frequently favored by musicians in action on stage. This paper explores potential issues that affect health preventive solutions for musicians. The acoustic control of a performance event, Jazz Live in Music House, is analyzed using the concept of sound map, and sound level measured across the event time. In addition, the psychological dimension of musicians in handling sound in their professional work environment will be explored in the terms of ‘performance ambition’.